Current Evidence for the Prevention of Endophthalmitis in Anti-VEGF Intravitreal Injections - P. ET. Lau; K. S. Jenkins; C. J. Layton (Journal of Ophthalmology)
Intravitreal injection of a therapeutic substance is the most common procedure performed in ophthalmology. It has a low incidence of serious complications but is associated with a small chance of endophthalmitis. Although the rate of endophthalmitis is between 0.019% and 0.09%, the associated visual morbidity is often devastating. Procedural changes have evolved over the years to improve patient comfort and reduce injection-related injury and infection. Despite the availability of published evidence, there remains considerable variations and lack of consensus in practical clinical settings. In addition, emerging literature concerning the use of speculums, the use of prophylactic topical antibiotics, and the setting of injections continues to impact the ophthalmologist’s injection practice. This article provides an up to date assessment of various aspects of the procedure such as the setting, ventilation, type of anaesthetic, and control of sterility during the procedure; including discussions on performing bilateral eye same-day injections and the use of antibiotics.